Adaptive relay autotuning under static and non-static disturbances with application to friction stir welding. (February 2020) - Taysom, Brandon S.; Sorensen, Carl D.
Abstract: When a traditional relay feedback test is biased, asymmetry is induced, erroneous system identification occurs, and the test may stop oscillating. Adaptive methods which restore symmetry to the relay test are developed, and additional methods are presented to detect and recover from a non-oscillation condition. This is demonstrated both in simulation and in a process with significant transients and disturbances — friction stir welding (FSW). In testing, it is shown that the adaptive method is able to restore symmetry even in the presence of severe and changing disturbances, including after the weld plunge where temperature gradients change rapidly. These improvements enable system identification of systems such as FSW in a more robust and accurate manner. Highlights: Relay feedback bias results in errant estimations and sometimes complete failure. The adaptive relay test removes bias from multiple sources. Recovery from non-oscillation is possible with minimal a posteriori knowledge. The adaptive relay test is robust and reliable. Once implemented, post-processing or expert-level knowledge is unnecessary.